The Role Of The Prosecutor's Office In Combatting Drug Crimes In North Sumatra - Hany Adhira Hadiyanti; Dianto Gunawan Tamba (Acta Law Journal, 2026)
Narcotics abuse and illicit trafficking remain serious problems in Indonesia, including in North Sumatra, because they threaten public order, social stability, and the future of younger generations. The complexity of narcotics crimes is not only reflected in the involvement of users or addicts, but also in the role of intermediaries, couriers, and dealers who maintain the circulation chain of narcotics. In this context, the Prosecutor's Office has a strategic position as a law enforcement institution responsible for pre-prosecution, prosecution, execution of court decisions, and preventive legal education. This article aims to analyze the role of prosecutors in tackling narcotics abuse in the jurisdiction of North Sumatra, examine prosecutorial actions against narcotics dealers, and identify the obstacles and efforts of the Prosecutor's Office in enforcing narcotics criminal law. This research uses an empirical juridical method with statutory and sociological approaches. The data are obtained from legal materials, journal articles, statutory regulations, and relevant field-based legal studies, then analyzed qualitatively. The results show that prosecutors play an important role in assessing case files, formulating indictments, proving criminal elements in court, determining proportional charges, and encouraging rehabilitation for eligible narcotics abusers. However, law enforcement faces several obstacles, including difficulty in distinguishing users from dealers, limited evidence, disconnected narcotics networks, lack of witnesses, inadequate facilities, and weak public participation. Therefore, the Prosecutor's Office must strengthen pre-prosecution, improve coordination with the Police and the National Narcotics Agency, enhance prosecutorial capacity, expand legal counseling, and balance strict punishment for dealers with rehabilitative measures for qualified abusers.